Analisis Tingkat Pendidikan, Pendapatan dan Religiusitas Terhadap Perilaku Konsumen Muslim di Kota Tangerang - Muhammad Najib Murobbi (Scimadly Publishing, 2023)
This study aims to find out how the level of education, income and religiosity affect the consumption behavior of Muslim households in Tangerang City. The analysis used in this research is quantitative with linear regression analysis method. The population sample includes people in Tangerang City within the scope of the household. The data collection instrument was through collecting questionnaires through social media. The results showed that the level of education had a significance value of 0.124 and income of 0.196 which had a value greater than 0.05 so that it did not have a significant effect. Meanwhile, the influence of religiosity has a significance value of 0.000 which indicates a value less than 0.05 so that it has a significant value on the consumption behavior of Muslim households in Tangerang City.